Daya Tarik Waduk Diponegoro Sebagai Sarana Rekreasi - Hanna Dian Pratiwi; Hadi Wahyono (Jurusan Perencanaan Wilayah dan Kota, 2017)
As one of the universities that are in great demand by the students, Diponegoro University always develops facility and infrastructures both to support academic activities and non-academic activities. One of the infrastructure facility built to support non-academic fields, namely the construction of Diponegoro Reservoir. Establishment of Diponegoro Reservoir which has the purpose to support the facility and infrastructures located in the campus of Diponegoro University, but also as a recreational facility for students of Diponegoro University. Reservoir area used as recreation area for students and community around the campus, proved by the students and residents who chatting, sports, and take pictures in the area. Although the area of Diponegoro Reservoir is not yet supported by adequate facility and infrastructure. From it can be known the attraction of Diponegoro Reservoir as a means of recreation. The purpose of this study is to determine the attractiveness and the factors that affect the students and the surrounding community for recreation in Diponegoro Reservoir. The method used is quantitative with descriptive analysis, and using factor analysis to know how big the relation of attraction level. Data collection techniques include questionnaires, document review, field observation and field documentation. The attraction of Diponegoro Reservoir includes 3 variables namely strategic location, atmosphere and supporting activities. Of the three variables can be concluded that the strategic location is the most first attraction seen by visitors so that have the desire to come to Diponegoro Reservoir.